Juana Manuela Gorriti's Narrative Creolization of Salta. Issue 3 (2nd September 2018) - Macintyre, Iona
ABSTRACT: Situated in the Andean borderlands of the northwest of Argentina, the province of Salta was a military hotspot for many years after the wars of independence broke out in 1810. This article explores the portrayal of this turbulent landscape in El pozo del Yocci and La tierra natal, two texts by Juana Manuela Gorriti (c.1818–1892), who was born into a prominent Unitarian family that lived in the region until being exiled to Bolivia in 1831 after federal rule. Gorriti would not return until 1884 but nevertheless celebrated and memorialized Salta's natural environment and its historical and cultural significance, so marked by conflict, in narratives that mourn a lost world, resuscitate forgotten histories of Creole sacrifice, and counter the traditional relegation of the interior in Argentinian culture.